Three phase optimisation for qualified and secured VMs for resource allocation. (2018) - Arivudainambi, D.; Dhanya, D.
Cloud computing services enable the users to use required computing resources for the required period which thereby permit the users to build a flexible information system. Choosing genuine and secured virtual machines (VM) among thousands of virtual machines is one of the main challenges in resource allocation to achieve higher accuracy. In this paper, VM optimisation techniques namely match making algorithm, memory aware VM and cuckoo technique is incorporated to select the best and secured virtual machine from cloud. In the proposed technique the first two are combined to select the best VM, where cuckoo is used to provide optimised resources to the finest VM. During the selection of finest VM from above techniques, it is necessary to select secured VM's to achieve an optimum result during resource allocation. To select secured VM, signature based detection and secure counters are employed to analyse network traffic and to monitor the data transactions.